Influence of atomic layer deposition temperatures on TiO2/n-Si MOS capacitor - Wei, Daming; Hossain, T.; Garces, N. Y.; Nepal, N.; Meyer, H. M., III; Kirkham, M. J.; Eddy, C. R. Jr.; Edgar, James H. (My University, 2013)
This paper reports on the influence of deposition temperature on the structure, composition, and electrical properties of TiO[subscript 2] thin films deposited on n-type silicon (100) by plasma-assisted atomic layer deposition (PA-ALD). TiO[subscript 2] layers ~20 nm thick, deposited at temperatures ranging from 100 to 300°C, were investigated. Samples deposited at 200°C and 250°C had the most uniform coverage as determined by atomic force microscopy. The average carbon concentration throughout the oxide layer and at the TiO[subscript 2]/Si interface was lowest at 200°C. Metal oxide semiconductor capacitors (MOSCAPs) were fabricated, and profiled by capacitance-voltage techniques. The sample prepared at 200°C had negligible hysteresis (from a capacitance-voltage plot) and the lowest interface trap density (as extracted using the conductance method). Current-voltage measurements were carried out with top-to-bottom structures. At −2 V gate bias voltage, the smallest leakage current was 1.22 × 10[superscript −5] A/cm² for the 100°C deposited sample.
Keywords: Deposition temperature; Atomic layer deposition; TiO2